Civil Liability by the National Land Agency (BPN) in the Protection of Personal Data on Electronic Certificates - Azzahra, Natasya Fhadyah; Rizkianti, Wardani (Jurnal Daulat Hukum, 2024)
This research aims to examine, study and explore the legal position of electronic certificate services (e-certificate) and personal data protection within the scope of legal arrangements. In addition, the author wants to encourage the responsiveness and responsibility of the National Land Agency (BPN) in organizing regulations and policies that are fair, certain and beneficial to land rights holders who are legal subjects, as mandated by the 1945 Constitution Article 28D Paragraph 1, Article 28G Paragraph 1 and Article 28H Paragraph 4. The policy of electronic land registration and issuance of electronic certificates organized by BPN is a step to improve land services in Indonesia through digital transformation which aims to provide a sense of security, justice and legal certainty for holders of land rights. However, many of these policies have created pros and cons in the community because the electronic system in Indonesia as a whole is still very vulnerable to cyber threats. Therefore, the importance of BPN's responsibility in providing legal certainty to land rights holders is regulated by legislation because until now the regulation does not exist so the author suggests the establishment of new regulations that contain the form and mechanism of responsibilities that must be carried out by BPN. This research uses an approach that has been used by other researchers, namely normative juridical with a statute approach and conceptual approach through literature studies analyzed descriptively qualitative. The problems to be answered regarding the regulation or legal basis of the implementation of the electronic land certificate policy and the limits of the responsibility of the BPN in providing legal certainty and justice to land rights holders.